Liabilities of designer towards variation cost in commercial buildings in Kuching, Sarawak / Nurlıyana Borhan and Ezlına Mohd Ahnuar - Borhan, Nurlıyana; Mohd Ahnuar, Ezlına (2018)
Variation order is inevitable in construction industry.There are various reasons contributing to the issuance of instruction requiring for variations. Among the reasons for variations is changes of reuirement from the client. This research is looking into the reasons caused by designers. The contention is that the client may have to incur unnecessary extra cost to complete the building due to the mistakes in design by the said designers. This research aims to determine the liability of designer towards variation cost in commercial buildings in Kuching, Sarawak. The specific objectives of this research are to investigate the common causes of variation orders by designers and to determine the liability of designers towards variation order. A questionnaire was sent to 89 respondents in Kuching, which comprise of consultant, contractor and client. Results shows that the top three (3) causes of variation order in the consultant's and contractor's perspectives are drawing modification, change in specification errrors and omission in design. All of these reasons were supported by court cases, in which it has been decided by the court that in the event of negligence on the part of the designers that subsequently causes the client to suffer losses, the designers may be held liable. From the client's perspective, drawing modification, conflicts between contract document and errors and omission in design were the main reasons for variation. As for the consequences, the clients is due to lack of information gave to designers, they had to develop design base on their perception.It can be concluded that none of the construction can be 100% completed according to the design or scope of work that has been agreed in the contract.